Particle size distribution, wet deposition and scavenging effect of per- and polyfluoroalkyl substances (PFASs) in the atmosphere from a subtropical city of China - Wang, Siquan; Lin, Xiaoping; Li, Qin; Li, Yongyu; Yamazaki, Eriko; Yamashita, Nobuyoshi; Wang, Xinhong (The Science of the total environment, 2022)
Per- and polyfluoroalkyl substances (PFASs) as emerging organic pollutants have received great attention, but the scavenging efficiency of particulate PFASs by wet deposition was rarely studied. For the first time, we reported the scavenging efficiency of PFASs on different particle sizes. In this study, both rainwater and particle samples were collected for a whole year from Xiamen, a subtropical city of China. Particulate PFASs ranged from 4.11 to 67.41 pg m−3, with an average value of 26.56 pg m−3, and perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA) were the main compounds. Perfluorocarboxylic acids (PFCAs) were predominantly observed on fine particles (<1 μm), while PFOS and 6:2 chlorinated polyfluoroalkyl ether sulfonic acid (6:2 Cl-PFESA) had large proportions on coarse particles (1–2.5 μm and 2.5–10 μm). In the rainwater, PFASs ranged from 0.20 to 180.65 ng L−1, with an average value of 10.71 ng L−1, and perfluorobutanoic acid (PFBA), PFOA were the main compounds. The wet deposition flux of ∑PFASs was 5200 mg km−2 yr−1, exhibiting high fluxes during the wet season (March to September). The scavenging efficiency of particulate PFOS and PFOA ranged from 68%–98% during the rainfall, and wash-out of the raindrops was found to be one of the main scavenging mechanisms. In addition, the precipitation duration and intensity influenced the scavenging efficiency. The scavenging capacity of PFCAs was large on fine particles, while for per-and polyfluoroalkyl sulfonic acids, the scavenging capacity was high on coarse particles. Our results showed that wet deposition effectively removed medium to long carbon chain (≥C6) PFASs in the atmosphere. [Display omitted] •PFSAs and PFCAs exhibited different particle size distribution.•Annual wet deposition flux of ∑PFASs was 5200 mg km−2.•Wet deposition effectively removed medium and long carbon chains particulate PFASs.•Wash-out of the raindrops was a scavenging mechanism.•Precipitation duration and intensity influenced the scavenging efficiency.